Gestión de talento humano y su incidencia en el desempeño laboral de la Agrícola e Industrial Villacrés Burbano del cantón Montalvo, periodo 2023 - Diaz Goyes, Fabian Fabricio (2025)
The Research will be carried out at the Agrícola e Industrial Villacres Burbano Company in the Montalvo canton, taking into account that its service is at the level of the province of Los Ríos. The main objective of the research is to analyze the management of human talent and its impact on the work performance of the Agrícola e Industrial Villacres Burbano in the Montalvo canton, during the period 2023, to improve productivity and the work environment. The methodological structure of this research is of an inductive type and is made up of mixed research components to obtain qualitative and quantitative information, which together will allow appropriate conclusions and hypotheses to be established and for the company to identify critical points of human talent management and make decisions based on the recommendations generated. This research project is directly related to the research guidelines established for the School of Administration, Commerce career, and considering the line of research: financial, administrative, tax, audit and control management, as well as the subline of research: administrative and financial management, the project is articulated with the pre-professional internship project: Comprehensive development of skills for the management of administrative, financial and service processes in public and private environments.